Investigation of growth rate dispersion in lactose crystallisation by AFM - Dincer, Tuna; Ogden, Mark; Parkinson, Gordon (Elsevier, 2014)
α-Lactose monohydrate crystals have been reported to exhibit growth rate dispersion (GRD). Variation in surface dislocations has been suggested as the cause of GRD, but this has not been further investigated to date. In this study, growth rate dispersion and the change in morphology were investigated in situ and via bottle roller experiments. The surfaces of the (0 1 0) faces of crystals were examined with Atomic Force Microscopy. Smaller, slow growing crystals tend to have smaller (0 1 0) faces with narrow bases and displayed a single double spiral in the centre of the crystal with 2 nm high steps. Additional double spirals in other crystals resulted in faster growth rates. Large, fast growing crystals were observed to have larger (0 1 0) faces with fast growth in both the a and b directions (giving a broader crystal base) with macro steps parallel to the (c direction). The number and location of spirals or existence of macro steps appears to influence the crystal morphology, growth rates and growth rate dispersion in lactose crystals.